"Upper Lip Response To Upper Incısor Retractıon; Comparıson Of Two Soft Tıssue Predıctıon Technıques In Growıng Patıents" - Oktay Üner; Emel Yücel Eroğlu (Galenos Yayinevi, 1991)
The objectives of orthodontic treatment are balance and harmony of facial lines, stability of the dentition after treatment, healthy oral tissues, and an effecient chewing mechanism. The study was designed to compare the accuracy of Economides' and Holdaway' techniques for the prediction of upper lip position which both have been developed to avoid the inadequacy of using a hard-tissue analysis alone for treatment planning and producing predictable and desirable facial esthetics. A total of 25 patients; 3 boys and 22 girls who received orthodontic treatment of the University of Gazi, Faculty of Dentistry Department of Orthodontics were selected for the study. Economides' and Holdaway' techniques for the prediction of upper lip position were applied and the treatment effects were examined on the tracing of the pretreatment and postretention cephalometric radiographs. The paired "t" test was applied to compare the accuracy of the above techniques to predict the upper lip position. The upper lip and the upper incisor position changes with treatment, the differences between the position of upper lip after treatment and predicted Economides' upper lip position; the differences between the popition of upper lip after treatment and predicted Holdaway' upper lip position, the differences between the errors of Holdaway' prediction and Economides' prediction were found to be statistically significiant. The standard error of prediction was 1.24 and the coefficient of reliability was 31% for Economides' prediction techniques. They were 0.85 and 58% for Holdaway' prediction tecnique respectively. The results of this study have been indicated that Holdaway' prediction technique was more accurate than Economides' technique to estimate the upper lip position.